RIPK3—a predictive marker for personalized immunotherapy? - Sigrun Smola (OncoImmunology)
Cancer immunotherapy is an attractive therapeutic option but it is currently unclear which patient may benefit from such approaches. Using the model of cervical cancer, we have demonstrated that PolyIC-driven immunogenicity strictly depends on the necroptosis regulator RIPK3 in the neoplastic cells. This proposes RIPK3 as a novel predictive marker for personalization of cancer immunotherapy